Does Firmography Patterns Human Resource Practice? Evidence from Microfinance Industry of India - Barpanda, Saswat; Mukhopadhyay, Susmita (Asian Journal of Empirical Research, 2020)
Broadness in organizational demography or firmography has a deeper impact on various organizational functions. Dual mission of Microfinance Institutions (MFIs) for financial profitability and social sustainability has led to obscuring human resource practices (HRPs). As a consequence, HR often fails to win the trust of business despite being the natural partner for driving sustainability. This study conceptualized the firmographic factors have a contextual impact on HR practices. The first part will explain the HRPs and challenge in the Indian MFIs. Keeping the wide variations of firmography in mind, the Indian MFIs varies in its level of maturity of the dimensions of HR practices. The second part of this study will explain and explores the concept of firmography through clustering technique. Multivariate regression has been used to understand the influence of Firmographic factors on the HR practices. Data has been collected through 250 MFIs across India to validate the findings which show a significant influence of firmography on the HR practices. The research would be useful for policymakers and micro finance practitioners to understand and strategize their human resource practices according to the firmographic context. This may ensure their humane and sustainable growth and justify their reason for their existing.